"Historiae Alexandrinae atque orientalis ita perita, ut eam epitomasse dicatur" (Hist. Aur. 30, 22). Powody, dla których autor "Historia Augusta" przypisał Zenobii autorstwo pracy historycznej = "Historiae Alexandrinae atque orientalis ita perita, ut eam epitomasse dicatur" (Hist. Aur. 30, 22). The reasons why the author of "Historia Augusta" ascribed to Zenobia the authorship of a historical work - Suski, Robert (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the biography of Zenobia, the author of "Historia Augusta" suggested that she knew well the history of Alexandria and the East, and that she wrote an epitome about this. In this situation, there are two possibilities. Zenobia could indeed have written such a historical work, or the author of "Historia Augusta" attributed it to her. The author made mistakes about the names of the Queen`s sons, so it is unlikely that he had any real knowledge about the Queen.
Keywords: historiografia rzymska; "Historia Augusta"; Zenobia; Kallinikos; Juwenalis (poeta rzymski; 60-130); Roman Historiography; Callinicus of Petra